Dynamic Changes of Arc Expression in Dorsal Striatum of Mice After Self-Administration of Sucrose - Li, Xue; Zhao, Jing-Wang; Ding, Qian; Wu, Cheng; Li, Wan-Qi; Guo, Yan-Chen; Wang, Di; Xu, Guang-Qing; Yuan, Ti-Fei; Gong, Wan-Kun; Lan, Yue (Frontiers in Cellular Neuroscience, 2021)
Region-specific plasticity in the striatal circuit plays an important role in the development and long-term maintenance of skills and sequential movement procedures. Studies investigating the molecular substrates that contribute to the plasticity changes during motor skill process have documented a transition in expression from the dorsomedial striatum (DMS) to dorsolateral striatum (DLS); however, few studies have explored the expression pattern of molecular substrates in the dorsal striatum during progression of instrumental learning. To address this issue, the activity-regulated cytoskeleton-associated protein (Arc) expressions in the subregional dorsal striatum were analyzed during the early and late learning phases of the 10-day sucrose self-administration process. We found that Arc protein is primarily detected in the DMS only in the initial learning stage; however, it is expressed in the DLS during both early and late learning stages. Moreover, Arc expression in the DMS correlated with the number of rewards received later in the training. These data indicated that the Arc expression in subregions of the dorsal striatum shows region-specific transfer and that Arc expression in the DMS contributes to obtaining reward in later learning stage during the process of instrumental learning.